Analisis Penggunaan Smartphone dalam Mengikuti Ibadah PA (Penelaahan Alkitab) Pemuda Pemudi di GKPPD Panji Bako Kabupaten Dairi Tahun 2024 - Ramot Slamat Limbong; Andar Gunawan Pasaribu; Nurelni Limbong; Robert Juni Tua Sitio; Warseto F. Sihombing (Journal New Light, 2025)
The purpose of this study was to determine and analyze the Use of Smartphones in Participating in Bible Study (PA) Worship for Young Men and Women at GKPPD Panji Bako, Dairi Regency in 2024. The research method used is qualitative research. The informant determination technique is purpose sampling based on certain criteria that are in accordance with the research topic. The data collection technique for this study is to use semi-structured interviews and documentation in the form of images. Based on the analysis of the interviews that have been conducted, the author found that the young men and women of GKPPD Panji Bako were greatly helped by the presence of Smartphones in worship. In today's digital era, smartphones have become an important tool that facilitates access to information and communication quickly and efficiently. This shows that the use of smartphones during PA worship can increase participant participation and involvement through easy access to Bible materials, supporting applications, and other digital resources. In addition, smartphones allow young men and women to interact and discuss in real-time through social media and instant messaging applications, which can enrich their understanding of the topics discussed. The results of the study also revealed that smartphones help overcome physical and geographical limitations, allowing young men and women who cannot be physically present to remain involved in PA worship through online streaming and video conferencing. Thus, the use of smartphones in the context of Bible study worship has the potential to support spiritual growth and build a more inclusive and connected community.